Transvascular transcatheter aortic valve implantation in 2017 - Gaede, Luise; Blumenstein, Johannes; Liebetrau, Christoph; Dörr, Oliver; Kim, Won Keun; Nef, Holger; Husser, Oliver; Gülker, Jan; Elsässer, Albrecht; Hamm, Christian W.; Achenbach, Stephan; Möllmann, Helge (Clinical Research in Cardiology, 2019)
Background: Transcatheter aortic valve implantation (TAVI) is emerging as the standard of care for patients with severe aortic stenosis. Recent results have been favourable even for patients with low periprocedural risk. Methods: We analysed the number of procedures, complications, and in-hospital mortality rates of all patients undergoing isolated aortic valve replacement in 2017 in Germany, focussing especially on transvascular (TV) TAVI. Patients were stratified according the German Aortic Valve Score (AKL) into the risk classes low, intermediate, high and very high (≥ 10%). Results: A total of 17,956 TV-TAVI and 9011 isolated surgical aortic valve replacements (iSAVR) were performed in Germany in 2017. Although the total rate of intraprocedural complications after TV-TAVI was the same as in 2016 (both 7.4%), fewer patients experienced an arterial vascular complication in 2017 (2017: 6.0%; 2016: 7.1%; p < 0.001). Likewise, the rate of new pacemaker implantation decreased (2017: 9.6%; 2016:11.4%; p < 0.001). In-hospital mortality after TV-TAVI and iSAVR was equal (2.7%) in 2017, despite the much higher risk profile of TV-TAVI patients. Using the AKL score as reference, TV-TAVI showed a more favourable observed-to-expected mortality (O/E) ratio (0.89) than iSAVR (1.14)- even more pronounced in patients at low risk (0.81 vs. 1.14). Conclusions: The rates of major complications like bleeding and permanent pacemaker implantation after TV-TAVI keep declining. In 2017 patients undergoing TV-TAVI had a low in-hospital mortality rate with an O/E ratio < 1, indicating that the results were again better than those of all TAVI and SAVR of the previous year. Graphic abstract: Overall in-hospital mortality after transvascular TAVI and isolated aortic valve repair 2017 in Germany stratified to risk groups by the German Aortic Valve Score (German AV Score/AKL Score): low risk group (AKL 0– < 3%), intermediate risk group (AKL 3– < 6%), high risk group (AKL 6– < 10%) and very high risk group (AKL ≥ 10%)[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-09
Keywords: AKL score; Aortic valve replacement; Mortality; Outcome; Surgery; TAVI